Trafficking of women in Entikong Sub-District Sanggau Regency, Indonesia - Mukhlis Mukhlis (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This study investigates and analyzes various phenomena related to transnational trafficking of women in Entikong Sub-District, Sanggau Regency, West Kalimantan, from the recruitment of the departure abroad to various human rights violations experienced by Indonesian women. The qualitative analysis method is used in this study. In general, trafficking of women in the Indonesia-Malaysia border regions is a phenomenon that arises due to the lack of legal protection, both while the victims are still in Indonesia and after they arrive abroad. This phenomenon has a negative impact on ensuring legal protection for women and the impact on the emergence of human rights violations (torture, harassment, exploitation, intimidation, rape, confinement, and forced sexual intercourse.).